Feature. (November 2018) - Ren, Jiaojiao; Zhao, Miaomiao; Liu, Baohua; Wu, Qunhong; Hao, Yanhua; Jiao, Mingli; Qu, Lemeng; Ding, Ding; Ning, Ning; Kang, Zheng; Liang, Libo; Liu, Huan; et al.
Abstract : N/A: The purpose of our research was to (a) identify sleep quality complications experienced by patients living with HIV infection and treated with antiretroviral therapy (ART), and (b) explore factors associated with sleep quality complications. From March to August in 2013, a cross‐sectional study was conducted at HIV‐designated hospitals in Harbin of Heilongjiang Province, China. Participants completed a questionnaire using the Spiegel scale to assess sleep quality; 32.1% of patients were negatively affected by sleep disturbances. Nighttime dreams and waking up were the most serious complications. We found that anxiety was the most prominent factor contributing to poor sleep quality, followed by ART medication types and family and social support. Patients with HIV infection and receiving ART experienced many different types of sleep complications. More attention should be given to the development of treatment guidelines for proper management of sleep disturbances experienced by patients with HIV.